Acústica de museus: uma proposta metodológica para subsídio ao processo projetual de salas com exposições permanentes - Barbo, Marselle Nunes (2023)
Museums are spaces for memory, appreciation, and, very importantly, the transmission of knowledge. Due to the variability of museum typology, the study of the acoustics of these spaces must be aligned with the needs of the exhibition model. This thesis aims to establish acoustic and design parameters for these buildings to balance reverberation, intelligibility at short distances, and speech decay based on the acoustic characterization of permanent exhibition museums. The parameters of free-plan offices were adopted, as was the testing methodology. Two permanent exhibition museums with different architectural typologies were studied: the Pinacoteca of São Paulo museum, housed in a century-old neoclassical building that originally housed a school, which was revitalized to become a museum. It has gallery-style rooms. The São Paulo Museum of Art (MASP) was built to be a museum in the modernist style. The exhibition method is contemporary, with works displayed on glass easels. Tests were carried out in museums for acoustic characterization and three-dimensional modeling, which allowed the development of scenario proposals that contribute to improving the acoustic quality of these spaces. The speech transmission index (STI) for native and non-native speakers, distraction distance (rD), clarity (C50), reverberation time, and A-weighted speech level (LP,A,S) were analyzed. The STI and rD parameters proved to be satisfactorily applicable to museums with permanent exhibitions. The reverberation time should be associated with the intelligibility and distraction distance parameters and used in the design process phase. The results for the clarity parameter (C50) were overestimated, while the LP,A,S showed little change between the receivers. The free-plan office test methodology can be applied to museums. It is concluded that using the proposals with the largest apparent absorption area (AT) is unnecessary since they increase intelligibility throughout the room, which is not the case for museums. As a prospect for future work, it is possible to continue the research with subjective studies.